Calderón de la Barca studies, 1951-69 : a critical survey and annotated bibliography - Parker, Jack Horace, 1914-; Fox, Arthur M. (University of Toronto Press, 2018)
The critical survey and annotated bibliography lists books and journal articles published on Calderon between 1951 and 1969. It continues the work on Calderon contained in W.T. McCready's bibliografia tematica de estudios sobre el Teatro Espanol Antiguo, and follows the pattern of the Lope de Vega Studies 1937-1962.